Relationship between thermal and sliding wear behavior of Al6061/Al2O3 metal matrix composites - Yimaz, Serdar Osman; Buytoz, Soner (Springer, 2007)
A16061 alloy and A16061/Al2O3 metal matrix composites (MMCs) were fabricated by stir casting. The MMCs were prepared by addition of 5, 10 and 15 wt% Al2O3 particulates and the size of particulates was taken as 16 mu m. The effect of Al2O3 particulate content, thermal properties and stir casting parameters on the dry sliding wear resistance of MMCs were investigated under 50-350 N loads. The dry sliding wear tests were performed to investigate the wear behavior of MMCs against a steel counterface (DIN 5401) in a block-on-ring apparatus. The wear tests were carried out in an incremental manner, i.e. 300 m per increment and 3,000 m in total. It was observed that, the increase in Al2O3 vol% decreased both thermal conductivity and friction coefficient and hence increased the transition load and transition temperature for mild to severe wear during dry sliding wear test.
Keywords: Al-Mg-Si; Abrasive Wear; Alloys; Deformation; Particles; Fracture; Strain; Steel; Fiber